Financial Development and the Patterns of International Capital Flows - von Hagen, Jurgen (Institutional Knowledge at Singapore Management University, 2010)
We develop a tractable, two-country, overlapping-generations model and show that cross-country differences in financial development can explain three recent empirical patterns of international capital flows: Financial capital flows from relatively poor to relatively rich countries while foreign direct investment flows in the opposite direction; net capital flows go from poor to rich countries; despite its negative net international investment position, the US receives a positive net international investment income. We also explore the welfare and distributional effects of international capital flows and show that the direction of capital flows may change along the convergence process of a developing country. Matsuyama (Econometrica 2004) argues that, in the presence of credit market imperfections, financial market globalization may lead to a steady-state equilibrium in which fundamentally identical countries end up with different levels of per-capita output. We show that this symmetry-breaking property depends crucially on the assumption that investment operates on the extensive rather than the intensive margin.